Competitive synergy through practicing triple bottom line sustainability: Evidence from three hospitality case studies - Boley, B.; Uysal, Muzaffer (Henry Stewart Publications, 2013)
This study advances the discussion of sustainability within the hospitality literature through the introduction of the concept of triple bottom line (TBL) sustainability and the potential synergistic benefits to competitiveness hospitality firms can achieve from practicing it. TBL sustainability transitions a firm's attention away from solely focusing on short-term profits to a concentration on the firm's long-term environmental, social, and economic performance. The study suggests that this transition to practicing TBL sustainability can result in “competitive synergy” for hospitality firms. The term “competitive synergy” is used to describe the phenomenon of when the anticipated benefits (e.g. reduced energy costs) from focusing on sustainability coalesce with the unanticipated benefits (e.g. increased employee job satisfaction) to make hospitality firms more competitive. One interviewee describes this synergy as a “resonant harmonic” because of the multiple benefits gained that were not part of the original motivations for engaging in sustainability. In an attempt to demonstrate industry examples of competitive synergy, three hospitality case studies practicing TBL sustainability are presented. These cases studies range from a small boutique hotel in Floyd, VA (Hotel Floyd), to a Caribbean resort in the Dominican Republic (Puntacana), and even to one of the world's largest hotel groups (InterContinental). Findings from the interviews highlight the many tangential benefits discovered from implementing sustainable initiatives aimed at environmental, social, and economic sustainability.